SISTEM INFORMASI PENDAFTARAN PENDAMPINGAN LEGALISASI PRODUK UMKM PROVINSI BANTEN BERBASIS WEB MENGGUNAKAN METODE SDLC PADA PKPH UNMA BANTEN - Agung Sugiarto; Susilawati Susilawati; Ropi Hidayat (Universitas Mathla’ul Anwar Banten, 2021)
The UMKM Legalization Assistance Registrasi Information System is a program specifically designed to make it easier for UMKM to register and assist the legalization of UMKM products. PKPH (Center for Halal Product Studies) is an institution that assists UMKM in product legalization This system is a system that explains product legalization registration for assistance to MSMEs. With this system, it is hoped that the management of UMKM can easily find out information on UMKM that will legalize their products. This information system is designed using Flow Of System (FOS), Contect Diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and uses the Tools Tets Editor Visual Studio Code with programming language and PHP Fremwork Laravel, HTML Language, CSS Using Bootstrap and Database using MySql. The results are in the form of Main Page, Registration, Scheduling, News and Admin menus. The application of this application is carried out by registering a domain that can be accessed anywhere with an internet connection By implementing this Registrasi System using the SDLC (System Development Live Cycle) method, it is hoped that it will be able to provide solutions for MSME administrators who carry out product legality.